In the name of the father? - Diogo Faria (Medievalista)
Prince João assumed some protagonism in the life of the kingdom of Portugal from 1471 onwards, when he was part of the army that conquered Arzila (North Africa), and successively increased his preponderance in governance until the end of the life of his father, King Afonso V. This article describes, analyses and seeks to interpret João's “escalation” in the political leadership of the kingdom with a focus on his participation in diplomatic activities. The preponderance he achieved during the war with Castile (1475- 1479) and the establishment of peace (1479-1480) stands out. This was a period in which he often acted autonomously and led political lines different from those defended by his father.